Hallucinogenic potential: a review of psychoplastogens for the treatment of opioid use disorder - Hornick, Mary G.; Stefanski, Ashley (Frontiers in Pharmacology, 2023)
The United States is entering its fourth decade of the opioid epidemic with no clear end in sight. At the center of the epidemic is an increase in opioid use disorder (OUD), a complex condition encompassing physical addiction, psychological co-morbidities and socioeconomic and legal travails associated with misuse and abuse of opioids. Existing behavioral and medication-assisted therapies show limited efficacy as they are hampered by lack of access, strict regimens, and a failure to fully address the nonpharmacological aspects of the disease. A growing body of research has indicated the potential of hallucinogens to efficaciously and expeditiously treat addictions, including OUD, by a novel combination of pharmacology, neuroplasticity and psychological mechanisms. Nonetheless, research into these compounds has been hindered due to legal, social and safety concerns. This review will examine the preclinical and clinical evidence that psychoplastogens such as ibogaine, ketamine, and classic psychedelics may offer a unique, holistic alternative for the treatment of OUD, while acknowledging that further research is needed to establish long-term efficacy along with proper safety and ethical guidelines.